The Effect of a PBL Interactive Physics Module on Student’s Collaboration Skills Based on Learning Styles - Putri Anggaraeni; Muhammad Arsyad; Abdul Haris (Jurnal Pendidikan Fisika, 2026)
This study was conducted based on the problem of low students’ collaboration skills in physics education at one of the senior high schools in Makassar and the need for innovative teaching materials that support active learning. The study aimed to analyze the effect of a PBL interactive physics module on students’ collaboration ability in terms of learning styles. This study used a quantitative approach based on a quasi experimental design. This investigation subjects consisted of an experimental class that received instruction using a PBL based interactive physics module and a control class that received instruction without the PBL interactive physics module. Data were collected through a learning style questionnaire, a collaboration skills observation sheet, and documentation. Data analysis was conducted using a two way analysis of variance (ANOVA). The analysis revealed that the utilization of the PBL interactive physics module had  a significant influence on students’ collaboration skills. Learning styles also had a significant influence on students’ collaboration skills. However, the interaction between the utilization of the PBL interactive physics module and learning styles did not have a significant influence on students’ collaboration skills. The results suggest that  the PBL interactive physics module is effective in developing students’ collaboration skills in physics education. Therefore, the implementation of PBL based interactive modules is recommended as an alternative instructional strategy to promote active learning and enhance collaboration skills in physics learning more broadly.